Hubungan Pengetahuan, Sikap, dan Dukungan Keluarga dengan Pemilihan Pertolongan Persalinan pada Ibu Nifas di Desa Sirnaresmi Kabupaten Sukabumi - Kristin Angraeni; Indah Sri Wahyuni; Eka Bati Widyaningsih (Indonesian Journal of Midwifery Scientific, 2026)
Background: The choice of birth attendant is a crucial factor in reducing maternal and infant mortality rates. In Indonesia, there are still mothers who choose traditional birth attendants (dukun/paraji), thereby increasing the risk of complications. Objective: To determine the relationship between knowledge, attitudes, and family support and the choice of birth attendant among postpartum mothers in Sirnaresmi Village, Sukabumi. Methods: A quantitative study with a cross-sectional design. A sample of 150 postpartum mothers (≤12 months) was selected using proportional random sampling. The instrument consisted of a questionnaire. Data analysis used the Chi-Square test and Odds Ratio. Results: There was a significant association between knowledge and choice of birth attendant (p=0.001; OR=4.815), attitude (p=0.001; OR=4.876), and family support (p=0.002; OR=3.965). Mothers with good knowledge, positive attitudes, and good family support tended to choose professional health personnel. Conclusion: Knowledge, attitude, and family support are associated with the choice of health personnel as birth attendants.